ONTOLOGICAL AND ANTHROPOLOGICAL ASPECTS OF THE CONCEPT OF HUMAN NATURE - R. Asha Nimali Fernando (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2011)
Anthropology is the study of the origin of the man. It is basically concern with the concept of Homo sapiens, and it is scientifi cally questioning what are human physical traits as well how do men behave and the variation among different groups of human with his social and cultural dimensions. Ontology is a subfi eld in traditional philosophy which is mainly focuses on the nature of being, existence or reality as such. There are some similarities and differences among these two areas. However when we deeply study the philosophical basis of the anthropology it is proof that it was derived from ontology.Anthropology discusses the social and cultural world or the physical entity of human nature. Ontology focuses the invisible aspect of human nature along with the ultimate reality. Therefore, it has a metaphysical aspect of human being; this philosophical notion has in fact, contributed to the development of the subject of anthropology. The present modern day has given very little attention to this philosophical combination of ontology to anthropology, rendering further investigation into the philosophical roots of anthropology.This research paper seeks to evaluate the relationship between ontology and anthropology by paying attention to the ontological arguments about the concept of man and human nature within Greek and modern western thoughts, in comparing with modern anthropological arguments.